Analysis of serum vitamin D and calcium levels in elderly patients with stable and unstable intertrochanteric fractures: A multi-center prospective study. - Kamran Alijanpour; Sina Afzal; Abolhasan Alijanpour; Hasan Barati; Hemmat Gholinia; Mehdi Tavassoli (PLoS ONE)
Background Hip fractures are highly prevalent in the elderly, with intertrochanteric (IT) fractures of the femur constituting about half of the fractures in this region. We aimed to evaluate the levels of serum calcium and vitamin D in patients with stable or unstable IT fractures to study their contribution to the severity of IT fracture. Materials and methods Using a prospective cross-sectional design, we enrolled patients with IT fractures admitted to two referral orthopedic centers in 2022. Unstable IT fracture was defined as those with reverse obliquity or a trans-trochanteric pattern of fracture, a large or comminuted posteromedial fragment, and subtrochanteric extension of the fracture. Serum 25 (OH) vitamin D and calcium levels were the main study variables assessed by lab tests and compared among the two study groups: stable and unstable IT fractures. Results A total of 286 patients with a mean age of 70.5 ± 7.3 years and a female predominance (60.4%) were included in the final analysis. Among the patients, 139 (48.6%) had stable IT fractures, and 147 (51.4%) had unstable IT fractures. The mean serum level of vitamin D was significantly higher in the stable group (30.3 ± 7.0) compared to the unstable group (26.5 ± 6.1) (P-value = 0.007). Increasing age was associated with a decreasing level of serum vitamin D; however, the association was weak and not statistically significant (P-value = 0.319). The mean serum calcium level was higher among stable cases (8.6 ± 0.7) compared to unstable cases (8.4 ± 0.9); however, the difference was not statistically significant (P-value = 0.540). Vitamin D and calcium levels were almost similar among males and females. Conclusion Lower levels of serum vitamin D were significantly associated with unstable IT fractures, and supplementation with this element might prevent severe fractures of this type and other fragility hip fractures.